Editorials new publications signed by university librarians from Bălţi in 2012 year (Confluenţe Bibliologice, 2026)
The article presents the editorial appearances signed by the librarians of the University of Bălța in 2012, highlighting their contributions to the development of scientific, bibliographic and informational activity. The publications reflect the professional involvement of librarians in research, the promotion of reading and the valorization of the university's documentary heritage.
Keywords: editorial activity; biobibliographies; thematic exhibition